Perspectives on the role of PTEN in diabetic nephropathy: an update. (2nd October 2020) - Khokhar, Manoj; Roy, Dipayan; Modi, Anupama; Agarwal, Riddhi; Yadav, Dharmveer; Purohit, Purvi; Sharma, Praveen
Abstract: Phosphatase and tensin homolog (PTEN) is a potent tumor suppressor gene that antagonizes the proto-oncogenic phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt) signaling pathway and governs basic cellular metabolic processes. Recently, its role in cell growth, metabolism, architecture, and motility as an intramolecular and regulatory mediator has gained widespread research interest as it applies to non-tumorous diseases, such as insulin resistance (IR) and diabetic nephropathy (DN). DN is characterized by renal tubulointerstitial fibrosis (TIF) and epithelial-mesenchymal transition (EMT), and PTEN plays a significant role in the regulation of both. Epigenetics and microRNAs (miRNAs) are novel players in post-transcriptional regulation and research evidence demonstrates that they reduce the expression of PTEN by acting as key regulators of autophagy and TIF through activation of the Akt/mammalian target of rapamycin (mTOR) signaling pathway. These regulatory processes might play an important role in solving the complexities of DN pathogenesis and IR, as well as the therapeutic management of DN with the help of PTEN K27-linked polyubiquitination. Currently, there are no comprehensive reviews citing the role PTEN plays in the development of DN and its regulation via miRNA and epigenetic modifications. The present review explores these facets of PTEN in the pathogenesis of IR and DN.